Distributed Voltage Unbalance Compensation in Islanded Microgrids by Using a Dynamic Consensus Algorithm - Lexuan Meng; Xin Zhao; Fen Tang; Savaghebi, Mehdi; Dragicevic, Tomislav; Vasquez, Juan C.; Guerrero, Josep M. (IEEE transactions on power electronics, 2016)
In islanded microgrids (MGs), distributed generators (DGs) can be employed as distributed compensators for improving the power quality in the consumer side. Two-level hierarchical control can be used for voltage unbalance compensation. Primary level, consisting of droop control and virtual impedance, can be applied to help the positive sequence active and reactive power sharing. Secondary level is used to assist voltage unbalance compensation. However, if distribution line differences are considered, the negative sequence current cannot be well shared among DGs. In order to overcome this problem, this paper proposes a distributed negative sequence current sharing method by using a dynamic consensus algorithm. In clear contrast with the previously proposed methods, this approach does not require a dedicated central controller, and the communication links are only required between neighboring DGs. The method is based on the modeling and analysis of the unbalanced system. Experimental results from an islanded MG system consisting of three 2.2-kVA inverters are shown to demonstrate the effectiveness of the method.